Are amphetamines helpful for adults with ADHD?. Issue 2 (February 2018) - Twomey, Michael; Webster, Laurisa; Beal, Matthew
Abstract : EVIDENCE‐BASED ANSWER : Amphetamine medications lead to large improvements in symptom severity in adults with attention deficit hyperactivity disorder (ADHD) over the short term; however, patients given amphetamines are more likely to stop treatment due to adverse events. Long‐term efficacy has not been established (SOR: A, meta‐analyses of RCTs).